1995
DOI: 10.1177/1073191195002001009
|View full text |Cite
|
Sign up to set email alerts
|

Personality Assessment Inventory (PAI) Scores of Lower-Socioeconomic African American and Latino Methadone Maintenance Patients

Abstract: The Personality Assessment Inventory (PAI) was administered to 229 lower-socioeconomic, methadone maintenance (MM) patients. Valid profiles were obtained from 160 subjects (70%). These indicated that the psychometric characteristics of the PAI were similar to those for the original standardization samples, except that internal consistency for the drug scale and three of seven nonclinical scales were only marginal. Comparisons of the PAI data with data obtained from the Diagnostic Interview Schedule and the Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
28
3
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 7 publications
7
28
3
1
Order By: Relevance
“…This assertion has been supported through such studies as Alterman et al (1995), whose treatment-seeking substance abusing sample obtained elevated DRG scores (M = 83.96), similar to the results for the inpatient substance abuse treatment sample (M =82.46) described by Hopwood, Baker, and Morey (2008). The DRG scale is moderately to highly correlated with the Drug Abuse Screening Test and the Addiction Severity Index …”
Section: Substance Abusesupporting
confidence: 70%
“…This assertion has been supported through such studies as Alterman et al (1995), whose treatment-seeking substance abusing sample obtained elevated DRG scores (M = 83.96), similar to the results for the inpatient substance abuse treatment sample (M =82.46) described by Hopwood, Baker, and Morey (2008). The DRG scale is moderately to highly correlated with the Drug Abuse Screening Test and the Addiction Severity Index …”
Section: Substance Abusesupporting
confidence: 70%
“…In comparison with community norms, Morey (1991) suggested that individuals enrolled in substance abuse treatment typically have markedly elevated DRG scores (i.e., range; 757-907). This assertion has been supported through such studies as Alterman et al (1995), whose treatment-seeking substanceabusing sample obtained elevated DRG scores (M = 83.96), similar to the results for the inpatient substance abuse treatment sample (M = 82.46) described by Hopwood et al (2008). The DRG scale has been shown to be moderately to highly correlated with the Drug Abuse Screening Test (Morey, 1991) and the Addiction Severity Index (Kellogg et al, 2002;Parker, Daleiden, & Simpson, 1999).…”
Section: Treatment Motivationsupporting
confidence: 56%
“…Other studies have demonstrated a relationship between RXR and treatment completion in forensic (Edens & Ruiz, 2005) and family medicine (Keeley, Smith, & Miller, 2000) samples and treatment length in an outpatient psychotherapy sample (Everson, 1998). RXR has also consistently been found to differentiate between community and clinical samples, in which treatment motivation is expected to be greater (Alterman et al, 1995;Boyle & Lennon, 1994;Cherepon & Prinzhorn, 1994;Morey, 1991). Finally, RXR has demonstrated significant negative correlations with several measures of treatment alliance (Baity, 2003;Blais et al, 2003) and a positive correlation with a measure of problem minimization (Anton & Reed, 1994).…”
Section: Instrumentmentioning
confidence: 88%